Three new species, one subspecies, and new records of the Oriental genus Loeblites Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2024)
Loeblites is a small genus of Oriental Scydmaeninae, currently comprising only five species distributed in Thailand, Malaysia (Sabah), China (Yunnan), and the Philippines (Mindanao). Loeblites anaiensis sp. n. (Sumatra), L. umphangensis sp. n. (Thailand), L. pseudominor pseudominor sp. n. (Borneo, Thailand), and L. pseudominor sumatrensis subsp. n. (Sumatra) are described. New records for L. sabahensis Franz in Sarawak are reported, a species so far known to occur only in Sabah. Identification key to species of Loeblites is given.